PEMBELAJARAN MENGGUNAKAN METODE EDoP UNTUK MENINGKATKAN PENGETAHUAN TENTANG PERTOLONGAN PERTAMA PADA KONDISI GIGITAN HEWAN BERBISA - Amni, Rahmalia; Aklima, Aklima; Fikriyanti, Fikriyanti; Tarigan, Abul A'la (Universitas Islam Negeri Alauddin Makassar, 2026)
Knowledge of first aid during a venomous animal bite is a skill that must be possessed by every individual, because this condition requires appropriate and immediate assistance at the scene. The right learning method will determine the success of the learning objectives. This study aims to analyze the effectiveness of learning using the EDoP (Education Demonstration and Practice) method on knowledge of first aid for venomous animal bites. The research design employed a one-group pre-posttest quasi-experimental study, which was analyzed using the Wilcoxon Signed-Rank Test. The research sample consisted of 50 adolescent students (12-18 years old) who were studying in junior high school and senior high school. The results showed that the majority of respondents fell into the Early Adolescence age category (53.3%), identified as female (56.7%), and had a senior high school education (58.3%). Before the intervention, 13.3% of respondents had low knowledge, and 15.0% had moderate. Then, after the EDoP intervention, 98.3% of respondents had high knowledge. The results of the Wilcoxon Signed Ranks test showed a significant difference between the percentage values ​​before and after the intervention (Z =−4.922; p < 0,001), so it can be concluded that the intervention provided suggests potential effectiveness in increasing respondents' knowledge in providing first aid in the event of a venomous animal bite.